Negotiating Religious Legitimacy and State Legality: Sirri Marriage in Islamic Family Law in Asam Jujuhan District - Burhanudin; Eli Martati; Nofialdi; Latif Aswen (KALOSARA: Family Law Review, 2026)
Sirri marriage remains one of the most troubling paradoxes in Muslim family life: religiously accepted by many communities, yet legally invisible in ways that often leave women and children unprotected. This study aims to examine the problem of sirri marriage in Asam Jujuhan District from the perspective of Islamic family law, with particular attention to its practice, the factors sustaining it, its legal consequences, and the limited use of the isbat nikah mechanism. Employing a qualitative phenomenological design, the research collected data through semi-structured interviews, observations, and documentation involving judges, KUA officials, religious counselors, local leaders, and couples engaged in sirri marriage. The findings show that sirri marriage persists not merely because of legal ignorance, but due to the interaction of geographical isolation, weak institutional access, administrative barriers, economic hardship, and limited legal awareness. The discussion reveals that while sirri marriage is regarded as valid under Islamic law when its essential elements are fulfilled, it remains unrecognized under state law, creating serious vulnerabilities for spouses and children, especially in relation to legal status, maintenance, inheritance, and civil documentation. The study concludes that sirri marriage in Asam Jujuhan reflects an unresolved tension between religious legitimacy and state legality, and that its persistence is rooted in structural and socio-legal constraints rather than in doctrine alone. The study implies the need to strengthen legal outreach, improve access to marriage registration, and optimize isbat nikah as an institutional bridge between Islamic family law and state legal protection.   Keywords: Islamic Family Law; Marriage Registration; Sirri Marriage.